2019
DOI: 10.1016/j.amsu.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of various limb salvage surgeries in osteosarcoma around knee: Megaprosthesis, extracorporeal irradiation and resection arthrodesis

Abstract: Background We evaluated the outcome and the survival rate of Limb salvage surgeries (LSSs) in osteosarcoma around knee by using megaprosthesis, ECI autograft, and modified arthrodesis of the knee with metallic plus bone cement (MAMC). Methods We reviewed 35 cases of osteosarcoma around the knee that was treated by megaprosthesis, ECI autograft and MAMC from 2012 to 2017. The survival, local recurrence, metastases, complications and functional MSTS score were evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Consistent with the results of previous studies, histologically, the common types of osteosarcomas seen were conventional, fibroblastic, and chondroblastic, 13 and the most common stage was the Enneking stage 2B. 5,15 Recent studies have shown that the 5-year survival rate for primary osteosarcomas is approximately 65%-70%, 16,17 although a survival rate of approximately 90% has also been reported. 18 Recent advances in chemotherapy and surgical treatments for osteosarcoma have improved the survival rates compared to those in the 1970s.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with the results of previous studies, histologically, the common types of osteosarcomas seen were conventional, fibroblastic, and chondroblastic, 13 and the most common stage was the Enneking stage 2B. 5,15 Recent studies have shown that the 5-year survival rate for primary osteosarcomas is approximately 65%-70%, 16,17 although a survival rate of approximately 90% has also been reported. 18 Recent advances in chemotherapy and surgical treatments for osteosarcoma have improved the survival rates compared to those in the 1970s.…”
Section: Discussionsupporting
confidence: 84%
“…4) could be the alternative methods of surgical reconstruction. Both methods have been found to result in a reasonable functional outcome even in later stages of the disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…JPS also has the advantage of being able to better protect the epiphyseal plate in certain pediatric OS patients [56], and thereby avoid the risk of causing a limb length discrepancy. These data, although also showing that extracorporeal irradiation is associated with lower functional outcomes and higher recurrence rates, may set the ground for JPS becoming the mainstream surgery in the future, with the refinement of existing surgical technologies [54,57].…”
mentioning
confidence: 90%